The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/fer-04-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

The role of big data in China’s sustainable forest management

Abstract: Purpose Forest as a vital natural resource in China plays an irreplaceable important role in safeguarding ecological security and human survival and development. Due to the vast territory, huge population and widespread forest landscape of China, forest management is a complex system involving massive data and various management activities. To effectively implement sustainable forest management, the big data technology has been utilized to analyze China’s forestry resources. Thus, the purpose of this paper is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
(33 reference statements)
0
20
0
1
Order By: Relevance
“…, 2021). Accurate data measurement and timely inventories obtained through precision forestry tools result in more reasonable and efficient decision-making (Hasan et al. , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2021). Accurate data measurement and timely inventories obtained through precision forestry tools result in more reasonable and efficient decision-making (Hasan et al. , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar to applications noted in SDGs 1 and 7, satellite imagery data have also been explored for sustainable forest management [200][201][202][203][204], i.e., identifying forest fire risk, monitoring deforestation, regional forest development planning and assisting forest management policy decision making, etc. Of relevance, the authors of [203] specifically focus on China, investigating the uses of Big Data in sustainable forest management, where they identify the relevant applications. The field of smart forestry is also addressed in [204], where the practical realization of Big Data analytics is examined.…”
Section: Big Data and Climate Actionmentioning
confidence: 99%
“…Recently, studies have shown how big data integration contributes as a technological compliance for massive information analysis on the unsuspected risk to occur. The future will largely depend on the concept of "datafication" and technological progress in terms of its creation and participation, as machines will communicate with each other via data networks, thereby reducing human participation in the process (Hasan et al, 2019).…”
Section: Big Data Integration Technologiesmentioning
confidence: 99%